Clinicopathological Significance of Poorly Differentiated Clusters in Liver Metastatic Lesions of Colorectal Carcinoma - PENG Hui; ZHANG Zhifa; WU Yingjun; ZHANG Xiaohan; ZHU Xianqiang; QIN Haili (Zhongliu Fangzhi Yanjiu, 2022)
Objective To investigate the clinicopathological significance of PDC in liver metastases and analyze the correlation of PDC between liver metastases and primary lesions. Methods Retrospective analysis of 72 matched cases of colorectal cancer with liver metastases was performed. The PDC in primary tumor and liver metastatic lesion was interpreted synchronously, and then the relationship between PDC in liver metastasis and clinicopathological parameters was analyzed based on the correlation of PDC between primary and metastatic lesions. In addition, PDC were interpreted in accordance with Uenos' standard. Results Among the 72 cases of liver metastasis of colorectal cancer, the number of G1, G2, and G3 graded by PDC was 28, 24, and 20, respectively. The PDC in liver metastatic lesion was correlated with tumor budding in liver metastatic lesion and PDC grade of primary lesion. No significant correlation with the size and number of liver metastatic lesion, the site, WHO grade, depth of invasion, lymph node metastasis, vascular invasion or tumor budding of the primary lesion was observed. Conclusion A positive correlation is found between liver metastasis of colorectal adenocarcinoma and PDC grade of primary tumor. Evaluating the PDC grade of primary tumor may provide a reference for the risk of liver metastasis.